2022
DOI: 10.3389/fmicb.2022.877884
|View full text |Cite
|
Sign up to set email alerts
|

Potential Fungi Isolated From Anti-biodegradable Chinese Medicine Residue to Degrade Lignocellulose

Abstract: Traditional Chinese medicine is one of the ancient medicines which is popular in Asian countries, among which the residue produced by the use of anti-biodegradables is endless, and causes significant adverse impacts on the environment. However, the high acidity of anti-biodegradable residues and some special biological activities make it difficult for microorganisms to survive, resulting in a very low degradation rate of lignocellulose in naturally stacked residues, which directly impedes the degradation of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The study screened 21 strains of cellulose-degrading bacteria, among which B. amyloliquefaciens (F16, F, F7) and B. velezensis (PX1) exhibited higher enzyme activity. Previous reports have confirmed that B. amyloliquefaciens and B. velezensis both exhibit strong cellulose degradation activity ( Hussain et al, 2017 ; Cheng M. et al, 2022 ). Li J. et al (2022) isolated a cellulase-producing strain, B. amyloliquefaciens DC-2, with an FPase activity of 7.31 U/mL, while the cellulose-degrading strains screened in this study exhibited high FPase activities ranging from 23.81 to 28.57 U/mL, indicating greater enzyme activity compared to strain DC-2.…”
Section: Discussionmentioning
confidence: 65%
“…The study screened 21 strains of cellulose-degrading bacteria, among which B. amyloliquefaciens (F16, F, F7) and B. velezensis (PX1) exhibited higher enzyme activity. Previous reports have confirmed that B. amyloliquefaciens and B. velezensis both exhibit strong cellulose degradation activity ( Hussain et al, 2017 ; Cheng M. et al, 2022 ). Li J. et al (2022) isolated a cellulase-producing strain, B. amyloliquefaciens DC-2, with an FPase activity of 7.31 U/mL, while the cellulose-degrading strains screened in this study exhibited high FPase activities ranging from 23.81 to 28.57 U/mL, indicating greater enzyme activity compared to strain DC-2.…”
Section: Discussionmentioning
confidence: 65%